Progress in Organosolv and Steam Explosion Pretreatments of Oil Palm Fibers for Biomacromolecules Extraction - Souza, Nágila F.; Almeida, Jéssica S.; Pinheiro, José A.; Pereira, Paulo H. F. [UNESP]; Saraiva Morais, João P.; Figueirêdo, Cléa B.; Azeredo, Henriette M.C.; Leitão, Renato C.; Rosa, Morsyleide de F. (Taylor & Francis, 2021)
Plant fibers are excellent sources of biomacromolecules, but the extraction of these chemicals critically depends on pretreatments on the biomass. In this work, steam explosion followed by acetosolv or ethanosolv pulping were evaluated as pretreatments for cellulose nanocrystal and lignin extraction from oil palm mesocarp fibers. The steam explosion improves defibrillation of the biomass, deconstructs lignocellulosic material, facilitating the separation between lignin and polysaccharides by organosolv pulping. The effects of acetic acid or sodium hydroxide concentrations and reaction time for acetosolv or ethanosolv pulping were evaluated by a central composite design. Fibers and biomacromolecules were characterized using analytical methods, including SEM, TEM, DRX, zeta potential, and FTIR. The optimized conditions to obtain cellulose nanocrystals from bleached acetosolv fibers (CNCA) were 80% (w/w) acetic acid catalyzed with HCl 0.6% (w/w) for 35 min, while the optimized conditions from ethanosolv fibers (CNCE) were NaOH 4% (w/v) and ethanol 95% (v/v) for 60 min. The lignins obtained from both optimized conditions presented high purity. The acetosolv delignification was more effective to extract the insoluble lignin (yield of 36.7%) than ethanosolv (yield of 23.2%). The CNCA and CNCE presented, respectively, high crystallinity (68% and 56%) and good aspect ratio (26 and 25).
Keywords: chemical analysis; green solvents; Lignin; nanocellulose; organosolv pulping; steam explosion